Ultrasound Anatomy of Lower Limb Muscles : A Practical Guide - Silvestri, Enzo; Muda, Alessandro; Orlandi, Davide (Springer International Publishing : Imprint: Springer, 2015)
The book provides a comprehensive description of the basic ultrasound principles, normal anatomy of the lower limb muscles and classification of muscle strain injuries. Ultrasound images are coupled with anatomical schemes explaining probe positioning and scanning technique for the various muscles of the thigh and leg. For each muscle, a brief explanation of normal anatomy is also provided, together with a list of tricks and tips and advice on how to perform the ultrasound scan in clinical practice. This book is an excellent practical teaching guide for beginners and a useful reference for more experienced sonographers.